PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PADA PT. PERTANI (PERSERO) UNIT PEMASARAN PADANGSIDIMPUAN - izzah, nurul (Institut Agama Islam Negeri Padangsidimpuan, 2017)
The relationship between producers and consumers is mutually beneficial where the quality of products becomes an attraction in making consumer buying decisions. Good product quality can help consumers make consumer buying decisions, so that consumers can be attracted to a product that is produced by a company will encourage consumers to purchase products with the quality and quantity offered by the research problem formulation is whether product quality has an effect on the decision of consumers to buy, to determine the effect of product quality on consumer purchasing decisions at PT. Pertani (Persero) Marketing Unit of Padangsidimpuan. This research is a quantitative descriptive study, using the SPSS Version 22.0 program. obtained the results of regression measurements with the equation KM = 12,363 + 0,519KP and R square data is 0,491 this means that the product quality variable is able to explain the consumer decision variables bought at PT. Pertani (Persero) Padangsidimpuan Marketing Unit is 49.1%, while the remaining 50.9% is influenced by other variables not discussed in this study. Hypothesis testing shows that there is a significant effect of product quality variables on consumer purchasing decisions, where t table (1,674) ≤ thitung (7,151).